Pembangunan Sistem Informasi Eksekutif Visualisasi Perencanaan Strategis Umkm Di Kota Cimahi - Lusy Sundary; Wina Witanti; Faiza Renaldi (Maranatha University Press, 2016)
Department of cooperatives and small micro enterprises Cimahi is one of the technical services that manage and exploit all the economic potential in the city of Cimahi either in the form of potential human resources and other resources through the empowerment of cooperatives Micro, Small and Medium Enterprises. Related to the process, there are some constraints in terms of data collection UMKM as a whole, one of them in terms of administrative data collection strategic planning. The process of making strategic planning carried out by UMKM. The process of making such a factor of success in the running of UMKM for a period of 5 to 10 years based on the reference contained in the strategic planning documents, the data renstra an UMKM that are not integrated with each other because dozens of UMKM in services with likely make difficulties in its management services. This study aims to establish an executive information system visualization for the preparation of strategic planning to facilitate the process of making strategic planning for UMKM Cimahi which can be integrated with the service cooperative UMKM, microfinance institutions and other related institutions